Assessment of Auditory Pathways Using Diffusion Tensor Imaging in Patients with Neurofibromatosis Type 1 - MEYDAN, SEDAT; MEYDAN, SEDAT; Aydin, Sinem; OTCU, HAFİZE; KİTİŞ, SERKAN; KİTİŞ, SERKAN; ALKAN, ALPAY; ALKAN, ALPAY (My University, 2018)
The aim of our study was to determine whether the diffusion properties of the auditory pathways alter between patients with Neurofibromatosis type 1 (NF1) and the healthy subjects. DTI can well demonstrate FA and ADC changes in auditory tracts and it may be a guide to identify the candidates for hearing loss among NF1 children.